(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: Diabetic nephropathy is the major cause of end-stage kidney disease in patients with diabetes mellitus. Objective: To identify risk factors for occurrence of Diabetic nephropathy among group of Iraqi children with type 1 diabetes mellitus. Methods: A cross-sectional study was conducted at Department of Chemistry and Biochemistry, and department of Pediatrics, College of Medicine, Al-Nahrain University from November 2019 to April 2020. Total of 80 children with diabetic nephropathy were divided into two groups: 40 patients without diabetic nephropathy and 40 patients with diabetic nephropathy. Blood and urine samples were taken for biochemical tests. Results: Each of age, duration of diabetes mellitus, fasting blood sugar and HbA1c were significantly associated with diabetic nephropathy. However, duration showed higher predictive value (OR = 18.69, 95% CI = 5.48-63.74, p